2014
DOI: 10.1111/hex.12306
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and nature of support in the personal networks of people with type 2 diabetes living in Europe: qualitative analysis of network properties

Abstract: Background Living with and self-managing a long-term condition implicates a diversity of networked relationships. This qualitative study examines the personal communities of support of people with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…For example, the desire for independence and autonomy may take precedence over the need for physical assistance, and act as a reason for not activating, or navigating support even when it is available. The preserving of a pre‐existing identity and roles in relation to specific close family ties (such as a son or daughter) or distrust and untrustworthiness of formal institutions may also preclude or promote the seeking and harnessing of support (Kennedy et al, ; Moore & McArthur, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the desire for independence and autonomy may take precedence over the need for physical assistance, and act as a reason for not activating, or navigating support even when it is available. The preserving of a pre‐existing identity and roles in relation to specific close family ties (such as a son or daughter) or distrust and untrustworthiness of formal institutions may also preclude or promote the seeking and harnessing of support (Kennedy et al, ; Moore & McArthur, ).…”
Section: Resultsmentioning
confidence: 99%
“…This more recent focus has highlighted a need to better understand how people engage with social capital, support and resources in a way that is acceptable and meaningful to them and members of their networks when managing and living with a long‐term condition. Here, we consider networks as personal communities that extend beyond patient and carer dyads to include a larger group of a community of interconnected individuals (such as friends and colleagues) that are strongly or loosely connected with one another [referred to as a network of networks (Vassilev et al, )].The dynamic of an individual operating within this type of networks may involve making decisions about when and who to contact, identifying and utilising resources that were previously underused, selecting some individuals over others, and providing a rationale that helps keep existing relationships content (Kennedy et al, ) This points to the need to explore the relationship between social capital and social support through paying greater attention to the process of engagement within social networks and the varying levels of collective efficacy of different networks, that is, their individual and collective capacity for such engagement (Vassilev, Rogers, Kennedy, & Koetsenruijter, ).…”
Section: Introductionmentioning
confidence: 99%
“…They also found that there are greater protective health and wellness benefits for those with a diverse social network that extend beyond health professionals and close family to incorporate casual acquaintances, friends, and groups than those with smaller or family centered networks. Within such diabetes care network, the “quality and nature of the relationships matter” (Kennedy et al., , p. 3173). The key to making such networks work is collaboration among the various actors.…”
Section: Typology Of Formal and Informal Network In Provision Of Diamentioning
confidence: 99%
“…Type 2 diabetes is an increasingly prevalent condition that is largely associated with self‐management requirements, including monitoring, diet and exercise . The demands of the self‐management of type 2 diabetes are described as challenging, and inadequate health behaviours may induce feelings of shame and guilt in this patient group …”
Section: Introductionmentioning
confidence: 99%
“…7 The demands of the self-management of type 2 diabetes are described as challenging, 8 and inadequate health behaviours may induce feelings of shame and guilt in this patient group. 9 To support individuals with chronic conditions, group-based self-management support has been initiated and is highly regarded in Western health policy as a cost-effective way to enhance health. 10 A broad definition of self-management support involves care and support from friends and wider community ties, 11 including groupbased activities, such as participating in an association, voluntary self-management support groups, or shared lay and professional education groups.…”
Section: Introductionmentioning
confidence: 99%